The modified 30-second chair stand test (m-30s-CST) is more sensitive than handgrip strength in detecting muscle strength changes and predicting physical performance in hospitalized geriatric patients - Walther M. W. H. Sipers; Martijn J.A. Rothbauer; Isis Ensink; Shannon Röhlinger; Audrey H.H. Merry (PLoS ONE, 2026)
Objectives To compare the modified-30s-Chair-Stand-Test (m-30s-CST) with handgrip strength (HGS) in measuring muscle strength in acutely ill geriatric patients. The aim of this study was to compare the responsiveness and predictive value of the m-30s-CST and HGS for physical performance and two-year mortality in hospitalized geriatric patients. Methods Responsiveness of the m-30s-CST and HGS was assessed in 92 patients (mean age 84 ± 6 years, 53.5% female) by comparing the performance at hospital admission and the day before discharge. These changes were then compared with changes in the ADL-Barthel-Index (ADL-BI) and Short Physical Performance Battery (SPPB). Results The number of repetitions on the m-30s-CST increased significantly during hospitalization in patients who improved on ADL-BI (n = 43) and SPPB (n = 33) and did not change in those who remained stable or worsened (ADL-BI: n = 32 and SPPB: n = 26). There was no significant change in HGS in either patients who improved on respectively ADL-BI (n = 43) and SPPB (n = 41), nor in those who remained stable or worsened (ADL-BI: n = 31 and SPPB: n = 34). The m-30s-CST showed a trend towards prediction of two-year mortality (AUC 0.609; P = 0,071) while HGS did not (AUC 0.573; P = 0.221). Two-year mortality was significantly higher in geriatric patients (n = 92) with less than 6 repetitions compared with patients with more than 5 repetitions on the m-30s-CST (HR 2.739; CI-95%: 1.173–6.396; P = 0.020). HGS according the EWGSOP-2 criteria was not associated with 2-year mortality (HR 0.969; CI-95%: 0.495–1.900; P = 0.928). Conclusion The m-30s-CST is superior to HGS for assessing changes in muscle strength and serves as a better proxy for physical performance, and is probably a predictor of two-year mortality in hospitalized geriatric patients.